Association between the vaginal and uterine microbiota and the risk of early embryonic arrest - Wang, Li; Chen, Junyu; He, Lin; Liu, Hanbo; Liu, Yan; Luan, Zonghui; Li, Hong; Liu, Weixin; Luo, Mengjun (Frontiers in Microbiology, 2023)
The aim of this study was to explore the microecological distribution and differences in the uterus and vaginal microbiome in women with early embryonic arrest and those with normal pregnancy by high-throughput sequencing. We systematically sampled the vaginal and uterine microbiomes of 56 pregnant women, namely, 38 patients with early embryonic arrest and 18 pregnant women with normal pregnancy-induced abortion. We obtained colonization data by 16S rRNA gene amplicon sequencing. In the vagina, Lactobacillus, Bacteroidetes and Helicobacter exhibited significant differences between the groups. We further found that Lactobacillus iners, Lactobacillus crispatus, Lactobacillus gasseri and Lactobacillus jensenii were the most dominant Lactobacillus species and that L. iners was significantly different between the groups. ROC curve analysis confirmed that Ensifer had the highest predictive value for early embryonic arrest. In the uterine cavity, we determined that Proteobacteria, Bacteroidetes, Firmicutes and Actinobacteria were the dominant bacteria at the phylum level and that Bacteroides, Pseudarthrobacter, Lactobacillus and Ralstonia were the dominant genera. Further classification of Lactobacillus revealed that L. iners, L. crispatus, L. gasseri, and L. jensenii were the main species. There was a significant difference in L. jensenii between the normal pregnancy group and early embryonic arrest group. Random forest analysis revealed 18 different genera in the uterus, and ROC curve analysis indicated that Candidatus Symbiobacter, Odoribacter, Blautia, Nocardioides and Ileibacterium had a certain predictive value.